Oral verrucous carcinoma - Krištofelc, Nejc (Radiology and oncology (Ljubljana), 2023)
Background. Verrucous carcinoma is a low-grade variant of squamous cell carcinoma with specific morphologic, cytokinetic and clinical features. Despite low mitotic activity and slow growth, it can infiltrate adjacent tissues in advanced stages but does not metastasize. The most frequently affected site is the oral cavity. The following article provides latest updates in the etiology, clinical presentation, diagnostics and treatment options in oral verrucous car-cinoma and discusses the existing dilemmas linked to this unique malignancy.Conclusions. Oral verrucous carcinoma must be differentiated from conventional squamous cell carcinoma due to its less aggressive behaviour with a more favourable prognosis. Close communication between clinician and patholo-gist is mandatory for making a correct diagnosis. Primary surgery with negative surgical margins seems to be the most successful treatment. However, management recommendations are not uniform since they are mostly based on case reports and small retrospective case series. Prospective and pooled multi-institutional studies are therefore needed.
Keywords: oral verrucous carcinoma; peroralni verrukozni karcinom; ploščatocelični karcinom; squamous cell carcinoma; verrucous carcinoma; verrukozni karcinom